Care for Critical Ill Patients With COVID-19: Establishment of a Temporary Intensive Care Unit in an Isolated Hospital - Peng, Milin; Qian, Zhaoxin; Zhang, Lina (Frontiers in Medicine, 2020)
The outbreak of COVID-19 has brought huge challenge and burden on the health care system in the worldwide. Due to its high contagion, the rapid increasing confirmed cases and the fast progressing of critically ill cases with COVID-19, there must be limited beds, specialized staffs, and medical resources in the limited critical care units. To ensure severe patients received standardized treatment, it is extremely important to establish temporary intensive care unit (ICU) in isolated hospital. The authors shared the experience of a temporary ICU establishment and management to care for critically ill patients with COVID-19 in Wuhan, including early identification the severity of critically ill patients, the characteristics of temporary ICU establishment, the training and protection of health workers and standardize treatment process.